PENINGKATAN KETRAMPILAN PEMERIKSAAN KANKER LEHER RAHIM DENGAN METODE IVA MELALUI REFRESHING KADER - Siti Rofiah; Rina Kusnanti; Ribkha Itha Idhayanti (Midwifery Care Journal, 2021)
Cervical cancer incidence ranks second after breast cancer. One of the efforts to detect cervical cancer early is the IVA method. The formation of IVA cadres in Bejiruyung Village was a breakthrough in efforts to reduce cervical cancer cases. Health cadres as the spearhead of health empowerment need to be refreshed in improving their skills. This study used an quasi experimental study with one group pre test post test design. Data analysis used Wilcoxon test. The results of the study showed that there are increased in cervical cancer examination skills using the IVA method through refreshing cadres in Bejiruyung Village, Sempor District, Kebumen Regency in 2020 (p value 0.0001). It is hoped that the Head of the Puskesmas will optimize health promotion officers at the puskesmas and village midwives in conducting training / refreshing for IVA cadres as well as health education / health promotion on early detection of cervical cancer using the IVA method. Village midwives should always assist and provide motivation to cadres in carrying out their duties to invite women to do early cervical cancer screening using the IVA method.